A Case Study on Exploring the Effects of Sales and Distribution - Yasir Mansoor (International Journal of Supply Chain Management, 2013)
The phrase world has now become a global village is rightly indicating the fruitful effects and outcomes of High sales and Profitability While; examining this Independent study first I will discuss the Abbott overall performance in Pakistan. Abbott is a 2 Billion company it has 33 towns in all over Pakistan which are working according to their demands and full filling the company needs. When this dilemma crop up there are unusual reasons behind thats. Whenever we have discuss this issue everybody have different opinions and conflict of interest but the problem of declining sales in still lying in Karachi warehouse and need to be resolved with true sprit. The problem can be Inventory or bad supply chain, meager branding, offensive marketing or may be motivation level of the sales team was not admirable. There are many factors behind this, may be one can true or all can true. An in-depth analysis of this situation will give us the exact idea. However, we believe that pitiable supply chain and ineffective inventory management is the foremost motive or may be one of the very important rationales which play a significant role behind this Sales issue but before initiate exertion on it we have to find what other say about that and for that we reviewed some literature and results. Consequently, there is a mixed opinion of different authors that Inventory is highly dependent on sales while some say it has a slight impact on sales but when we apply some statistical tools thats are regression and co-relation we found that Inventory is highly dependent on Forecasted Sales and working Capital but it has a very slight impact on Sales. There are several other reasons of declining sales. While, Conducting a Regression and Co-relation analysis it is proved that working capital and Forecasted sales are highly reliant on Inventory level whereas, it has no significant impact on Sales. There are assorted reasons of moribund Sales.